Pengaruh Disiplin dan Budaya Organisasi Terhadap Kinerja Karyawan pada PT Manorian Engineering Prakarsa di Kabupaten Tangerang - Maulana Rizky Andhika; Risza Putri Elburdah (Indo Publishing, 2025)
This study aims to analyze the influence of work discipline and organizational culture on employee performance at PT Manorian Engineering Prakarsa, Tangerang Regency. The research method used is quantitative with a descriptive associative approach. The sampling technique applied is saturated sampling, where all 76 employees are used as research respondents. Data were collected through questionnaires, and analyzed using validity, reliability, classical assumption tests, multiple linear regression, t-test, F-test, and determination coefficient (R²) with SPSS version 26. The results show that work discipline has a significant effect on employee performance with a t-value > t-table (2.804 > 1.669) and significance value 0.006 < 0.05. Organizational culture also significantly influences employee performance with a t-value > t-table (2.961 > 1.669) and significance value 0.004 < 0.05. Simultaneously, both variables significantly affect employee performance, as indicated by an F-value > F-table (8.579 > 3.12) and significance value 0.000 < 0.05. The determination coefficient (R²) of 0.197 indicates that work discipline and organizational culture contribute 19.7% to employee performance, while the remaining 80.3% is influenced by other factors beyond this study. Therefore, it can be concluded that work discipline and organising culture have a positive and significant influence on improving employee performance at PT Manorian Engineering Prakarsa.